Development of a four-step switching technique for operation of PWM ac controller / Abdul Rahim Ahmad - Ahmad, Abdul Rahim (1995)
Solid state ac controllers are widely used as ac power main regulators in various applications. Recently, Pulse Width Modulation (PWM) switching techniques have been employed for improved performance of the regulator. In particular, a four-step switching technique has proven to be effective in realizing a higher power PWM operated ac controller, In this work, an ac controller employing the above technique is developed and tested.